Analysis of Alternative Splicing Events and Identification of Key Genes in Brassica napus Leaves Infected by Leptosphaeria biglobosa - Xinning Ma; Lin Yuan; Jiuru Huangfu; Mengjiao Yan; Chen Guo; Lili Zhao; Hongxia Sun; Xiaoqing Jia; Ziqin Li; Haiyan Huangfu (Agronomy, 2024)
Alternative splicing (AS) is a prevalent post-transcriptional regulatory mechanism in eukaryotes and plays a crucial role in plant disease resistance. Here, we used the Illumina Novaseq sequencing platform to conduct transcriptome sequencing on canola (Brassica napus) leaves infected with the blackleg pathogen (Leptosphaeria biglobosa strain nm−1) at 0 h, 72 h, 120 h, and 168 h post-inoculation to investigate the mechanism of AS coordination with transcriptional regulation in canola’s response to blackleg disease. The rMATS software (4.1.0) was employed to analyze different AS events in samples taken at 72 h, 120 h, and 168 h. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were performed to elucidate the biological functions of differentially spliced genes at various time points, while Weighted Gene Co-expression Network Analysis (WGCNA) was used to identify key modules and hub genes. As a result, our analysis reveals 16908 AS events across three time points, with 221 being differently spliced. Intron retention (RI) was the most common AS event, accounting for approximately 55% of all events, while alternative 5′ splice site events were least common, comprising only 2%. Furthermore, a total of 213 significantly differentially spliced genes were identified, which were enriched in functions related to protein kinase activity, transferase activity, and pathways such as MAPK signaling pathway—plant and plant hormone signal transduction. WGCNA identified three key modules and ten hub genes, including calcium-binding transcription activator 1, LRR class receptor serine/threonine protein kinase FEI 2, PLATZ transcription factor family proteins, serine/threonine protein kinase PRP4, and E3 ubiquitin ligase SUD1, all of which are associated with canola resistance to L. biglobosa. Thus, this study provides a theoretical basis for identifying disease-resistance genes involved in AS and for exploring the functions of AS gene isoforms in canola.